Growth of the telescope snail, telescopium telescopium (Linne) in brackishwater ponds. - Apistar, Jobert Hopanda
Samples of T. telescopium were collected every month from April to October 1997 for six months, in brackishwater ponds. Allometric relationships were defined by comparing shell lenght with shell width, as well as various body weight proportions including total weight with shell, total volume, visceral weight and visceral volume. A total of 5 cohorts with growth rates ranging from 0.45 - 0.67 mm. day were observed using the Bhattacharya analysis. A high mean growth rate of 0.56 mm.day (sd + 0.07, n=5) was estimated by joining the modes of the cohorts between successive sampling months. Low inverse correlations were observed between mean shell lenght and various environmental parameters (i.e., salinity, air temperature, water temperature and organic matter content) possibly explained by the species' environmental adaptations. On the other hand significant correlation was observed between mean shell lenght and density, indicating the possible role of overcrowding in these habitats.